ANALISIS DAN PENGUJIAN KEAMANAN JARINGAN VLAN BERBASIS FIREWALL SECURITY PORT: ANALYSIS AND TESTING OF VLAN NETWORK SECURITY BASED ON FIREWALL SECURITY PORT - Muhammad Attalla Noval Bijaksa; Subektiningsih Subektiningsih; Pramudhita Ferdiansyah (LPPM Universitas Abdurrab, 2025)
The rapid advancement of computer network technology and the increasing demand for efficient, stable, and high-speed network access, along with the need for adequate security measures, network security has become a major concern. Network security encompasses various techniques designed to protect and maintain the integrity of network systems. One such technique involves implementing a firewall system that incorporates the port security method. This method is used to regulate the use of network ports with the aim of controlling unauthorized access to the network. Port security also serves to block suspicious access, monitor network activity, and prevent data theft by malicious actors. By implementing a firewall system based on port security, potential issues within the network infrastructure can be mitigated, thereby enhancing the overall quality of network security. This study analyzes the reliability of a firewall system that utilizes a port security approach. The test results demonstrate that Macof attacks were unable to compromise the switch’s MAC address table, which was protected by Sticky Port Security.